Assessment of the extent of oxidative stress induced by intravenous ferumoxytol, ferric carboxymaltose, iron sucrose and iron dextran in a nonclinical model - Toblli, E Jorge; Cao, Gabriel; Oliveri, Leda; Angerosa, Margarita (Arzneimittelforschung, 2011)
Intravenous (i. v.) iron is associated with a risk of oxidative stress. The effects of ferumoxytol, a recently approved i. v. iron preparation, were compared with those of ferric carboxymaltose, low molecular weight iron dextran and iron sucrose in the liver, kidneys and heart of normal rats. In contrast to iron sucrose and ferric carboxymaltose, low molecular weight iron dextran and ferumoxytol caused renal and hepatic damage as demonstrated by proteinuria and increased liver enzyme levels. Higher levels of oxidative stress in these tissues were also indicated, by significantly higher levels of malon-dialdehyde, significantly increased antioxidant enzyme activities, and a significant reduction in the reduced to oxidized glutathione ratio. Inflammatory markers were also significantly higher with ferumoxytol and low molecular weight iron dextran rats than iron sucrose and ferric carboxymaltose. Polarographic analysis suggested that ferumoxytol contains a component with a more positive reduction potential, which may facilitate iron-catalyzed formation of reactive oxygen species and thus be responsible for the observed effects. Only low molecular weight iron dextran induced oxidative stress and inflammation in the heart.
Keywords: Ferric carboxymaltose; Ferumoxytol; Inflammation; Intravenous iron; Iron sucrose; Oxidative stress